1) Выполните умножение: 2a * (-3ax^2) * (-5x^3)

2) Решите уравнение: 1/3(6x-1) - (0,5 - x/2) = 0

1

Ответы и объяснения

  • Участник Знаний
2013-08-06T23:42:56+04:00
2.
Ну во первых минус на минус - даёт плюс 
2a * (-3ax^2) * (-5x^3)=2a * 3ax^2 * 5x^3
Распишу подробно, по действиям:
1)  2a * 3ax^2 = a*6ax^2 = 6a^2x^2
2) 6a^2x^2 *  5x^3=30a^2x^{3+2}=30a^2x^5

2.
1/3(6x-1) - (0,5 - \frac{x}{2}) = 0
 \\\\ \frac{6x-1}{3}-0,5+\frac{x}{2}=0
 \\\\\frac{6x-1}{3}+\frac{x}{2}=0,5
 \\\\ \frac{12x-2+3x}{6}=0,5
 \\\\ \frac{15x-2}{6}=0,5
\\\\15x-2=0,5*6
 \\\\ 15x=3+2
\\\\x=5/15
\\\\x= \frac{1}{3}